Three-dimensional finite element analysis of geosynthetic-reinforced soil walls with turning corners. Issue 3 (June 2021) - Hung, C.; Liu, C.H.; Liu, H.
Abstract: The paper presents in-depth three-dimensional finite element analyses investigating geosynthetic-reinforced soil walls with turning corners. Validation of the 3D numerical procedure was first performed via comparisons between the simulated and reported results of a benchmark physical modeling built at the Royal Military College of Canada. GRS walls with corners of 90°, 105°, 120°, 135°, 150°, and 180° were simulated adopting the National Concrete Masonry Association guidelines. The behaviors of the GRS walls with corners, including the lateral facing displacement, maximum reinforcement load, factor of safety, potential failure surface, vertical separation of facing blocks, and types of corners were carefully evaluated. Our comprehensive results show (i) minimum lateral displacement occurs at the corner; (ii) lower strength of reinforcements are required at the corner; (iii) higher corner angles lead to lower stability; (iv) potential failure surface forms earlier at the end walls; (v) deeper potential failure surfaces are found at the corners; (vi) larger numbers of vertical separations are found at walls with smaller corner angles. The paper highlighted the salient influence of the corners on the behaviors of GRS walls and indicated that a 3D analysis could reflect the required reinforcement length and the irregular formation of the potential failure surfaces. Highlights: The minimum lateral displacement always occurred at the turning corner. The larger the corner angle, the smaller the deformation difference throughout the sections of the GRS walls. Less strength of reinforcement was required in the corner than to the end walls, and the required strength of the reinforcement increased with increasing turning corner angle. The smaller the corner angle, the higher the FOS, suggesting that a conventional 2D (plane-strain) analysis may underrepresent the existence of the corners. Reflected by the 3D analyses, the potential failure surface grew deeper near the turning corner, indicating that a longer required length of reinforcement should be adopted at the corner. The effects of the turning corner, in terms of lateral facing displacement, maximum reinforcement load, FOS, potential failure surface, and vertical separation of facing blocks, were less significant at larger angles.